Bioactive Potentials of Cassia renigera Benth. Extracts against the Stored Product Pests Callosobruchus chinensis L., Sitophilus oryzae L. and Tribolium castaneum (Hbst.) - Nesa, M.; Islam, S.; Sharma, S. K.; Rekha, S. B.; Ferdous, J.; Islam, N. (Journal of Scientific Research, 2017)
Petroleum (Pet.) ether, CHCl3 and CH3OH extracts of Cassia renigera Benth. were tested against Callosobruchus chinensis L. for dose-mortality and repellency; and against Sitophilus oryzae L. and Tribolium castaneum (Hbst.) for repellent activity test. The Pet. ether extract of leaf was found active against C. chinensis adults through dose mortality assay and the LD50 values established were 9.270, 4.932, 2.032, 1.721, 1.671, 1.543, 1.513, 1.503 and 1.478 mg cm-2 for 0.5, 6, 12, 18, 24, 30, 36, 42 and 48 h of exposure respectively. However, the leaf extracts of CHCl3 and CH3OH; as well as the Pet. ether, CHCl3 and CH3OH extracts of the stem-bark did not give mortality to the test organism. The CHCl3 extract of leaf showed repellent activity against Tribolium castaneum at 0.1% level of significance (P < 0.001), and the Pet. ether extracts of the leaf and the CH3OH extracts of the stem-bark offered repellency at 1% level of significance (P < 0.01) between dose levels. Only the CHCl3 extracts of the stem-bark gave repellency at 5% level of significance (P < 0.05), while the CH3OH extracts of leaf and Pet. ether extract of stem-bark did not show any significant repellency at all.